Petrology of amoeboid olivine aggregates in Antarctic CR chondrites: Evidence for aqueous alteration and shock metamorphism. - Mutsumi, Komatsu; T., J. Fagan; A., Yamaguchi; T., Mikouchi; M., Yasutake; M., E. Zolensky (2017)
第8回極域科学シンポジウム/個別セッション：[OA] 南極隕石 12月6日（水）国語研究所 2階講堂 The Eighth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites Wed. 6 Dec./2F Auditorium, National Institute for Japanese Language and Linguistics conference object